Female leadership: Facilitators, barriers and the road to inclusion - Reyes Cornelio, Roberto; Cruz Velazco, Jessica Esther; Aguilar Morales, Norma (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2025)
OBJECTIVE: To identify the key factors that facilitate female leadership and the barriers that limit their full integration into the management environment, as well as to assess their impact on organizational inclusion.MATERIAL AND METHOD: A systematic literature review was conducted, analyzing 39 articles published between 2023 and 2024. Databases such as Web of Science, Emerald and Elsevier were used, applying specific inclusion criteria to ensure the relevance and timeliness of the sources. Data analysis was carried out using ATLAS.ti software, which facilitated the coding and categorization of the findings.RESULTS: Female leadership was found to be characterized by qualities that bring significant value in the business environment, such as a strong sense of ethics, adaptability, and a focus on collaboration. In addition, cultural, organizational, and structural barriers were identified that limit the advancement of women into leadership positions.CONCLUSIONS: Female leadership not only enriches decision making but also promotes a collaborative and inclusive work environment. It is crucial to implement policies that foster inclusion and overcome existing barriers.
Keywords: female leadership; organizational inclusion; women.